(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Covid -19 pandemic & lockdown has cause deliberate effect to human’s physical & mental health & trigger many psychological problems like anxiety, loneliness, stress, depression & other panic disorder. The investigators interested to find out the psychological impact of lockdown among general population & correlation with different components of modified psychosocial impact event scale. Researchers have used non – experimental descriptive research deign with Non – randomized convenient sampling & 500sample recruited for the study. Researchers have used standardized modified impact event scale in the form of 5 point likert scale, they have identified that 366 sample(73.2%)have moderate stress,110 sample (22%) identified with severe stress & remaining 24 sample (4.8%) have mild stress. Another finding revel that each component having positive correlation with each other. The significant association of psychological impacts & selected demographic variables were found with use of modified impact event scale. Researcher have concluded that this type of event or diseases outbreak affect the mental health of the person , increased stress among individual & also affect the daily life of the person.